Porous graphene coating by solid phase reaction and its virucidal application - Gupta, Vikaskumar Pradeepkumar; Furunaga, Takuya; Hinatsu, Masako; Hayashi, Kyoko; Kudkyal, Vyankatesh Ramlu; Yaakob, Yazid; Asaka, Toru; Mohd Yusop, Mohd Zamri; Yang, Yong; Kawahara, Toshio; Hihara, Takehiko; Tanemura, Masaki (Elsevier, 2025)
For a wider range of applications of porous graphene, including the functionalization of the surface of daily items, its direct coating onto the surface is highly demanded. Here, we demonstrated porous graphene coating by simple vacuum annealing of Co–C based films on SiO2/Si substrates at 800 °C. The porous graphene films thus prepared featured a dense distribution of core-shell structures consisting of an empty core surrounded by a multilayer graphene shell (hollow graphene shell), together with dispersed Co nanoparticles. Adding a tiny amount of Ag (<∼1 atomic %) led to a more pronounced distribution of the hollow graphene shell, as well as a dispersion of finer Co nanoparticles, due to the faster agglomeration and evaporation of Ag than Co. Aqueous extracts of Sargassum horneri loaded onto the porous graphene films thus prepared showed excellent virucidal activity against the influenza virus, even after the test piece had been rinsed (with a residual virus rate of ∼0.4 %). This direct porous graphene coating method is, in principle, applicable to any heat-tolerant substrates independent of the shape. Thus, this method is promising for direct porous graphene coating applications that is useable even in the harsh working conditions of liquids.